Philanthropic Practices and Zakat Distribution Mechanisms for Equal - Rufaida, Alfi Maulissa; Purnama Sari, Yesa Tiara; Agustina, Ruswanda; Utami, Anida Aulia (International Conference on Islamic Economic (ICIE), 2024)
This article aims to analyze Philanthropic Practices and Zakat Distribution Mechanisms: Evaluation of Efficiency, Equity and Transparency in Social Fund Management. The method used is a qualitative method.In this article, the data source obtained is a written source related to Philanthropic Practices and Zakat Distribution Mechanisms: Evaluation of Efficiency, Equity and Transparency in Social Fund Management. The type of data used in this article is qualitative data.Data collection in the article uses literature study techniques by collecting books and journals related to Philanthropic Practices and Zakat Distribution Mechanisms: Evaluation of Efficiency, Equity and Transparency in Social Fund ManagementData analysis in this article uses narrative techniques.Philanthropic Practices and Zakat Distribution Mechanisms: Transparency in the Management of Social Funds based on research that has been conducted that the practice of Islamic Philanthropy is manifested in the practice of generosity through (ZISWAF) zakat, infaq, alms and waqf, as well as in the distribution of philanthropy the policy has been established by LAZISMU that There are several categories that are prioritized, including needy, needy, and fisabilillah.There are two approaches to distributing zakat funds, namely the partial approach, where the funds are given directly to the needy and needy for urgent needs.A structural approach that emphasizes the allocation of zakat funds by providing funds periodically to alleviate economic poverty.This requires strong governance mechanisms and a high level of accountability. Financial reporting is transparent and carries out regular audits of zakat institutions to ensure proper use of zakat funds.